Model evaluasi pembelajaran fiqih: Kajian teoritis terhadap ranah kognitif, afektif, dan psikomotorik - Azwa, Nurul; Aini, Nur; Zaman, Nurul (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to examine the theoretical model of fiqh learning evaluation with a focus on the integration of three main domains: cognitive, affective, and psychomotor. Evaluation in fiqh learning is not only intended to measure the mastery of Sharia law knowledge but also to assess the internalization of religious values and the practical worship skills of students. This study uses a library research method with a descriptive-qualitative approach, through content analysis of relevant literature in the form of books, scientific journals, and previous research results. The results of the study show that a comprehensive evaluation of fiqh learning must combine the three domains in a balanced manner. The cognitive domain is measured through written tests and analytical projects; the affective domain through attitude observation, self-assessment, and reflective journals; while the psychomotor domain through work samples and worship practice skill rubrics. The integration of these three domains into a single evaluation model produces a more authentic, valid, and meaningful assessment because it assesses the aspects of “knowing, being, and doing” as a whole. The conclusion of this study emphasizes the need to apply an integrative evaluation model in fiqh learning in order to achieve a balance between knowledge, faith, and practice in shaping the religious character of students.